Processing and storage of blood components during the COVID-19 pandemic - Antić, Ana; Živković Đorđević, Sanja; Jelić, Marija; Vučić, Miodrag; Vacić, Nebojša; Balint, Bela (Medical Word, 2021)
The spread of the COVID-19 virus has a strong influence on blood collection, maintaining a stable supply of all blood components and the safety of the transfusion itself. SARS-CoV-2 has a long incubation period (1-14 days, on average 5-6 days, longest reported 24 days) and causes asymptomatic infection in a large number of patients, which is a great challenge in a recruitment of blood donors and achieving a safe transfusion. Precise recommendations and precautions have been adopted regarding the criteria for temporary refusal of blood donors during the COVID-19 pandemic, organization of mobile teams and collection sites, disposal of medical waste, examination of potential donors and mandatory body temperature measurement. Although transmission of COVID-19 via blood and blood components has not been demonstrated, some countries have also introduced mandatory NAT testing for SARS-CoV-2 as a part of blood screening testing. Also, proactive measures have been taken, such as temporary storage of blood in quarantine for 14 days after collection, while special attention is paid to efficient management of blood component stocks and development of a collection plan, in order to avoid shortage of certain blood components or their expiration. The first step in this regard is to revise the measures which have the aim for improving the usability of blood components, ie reducing waste of stocks, which primarily refers to the temporary extension of the shelf life of blood components. Extending the shelf life of erythrocytes (longer than 35 to 49 days, which is defined at the national level) should be considered as early as possible, because once a shortage of erythrocytes occurs, they will be issued long before the expiration date. Previous studies have not shown significant side effects of erythrocyte transfusion with extended shelf life, so it is possible to consider the flexibility of blood processing and erythrocyte storage conditions with mandatory internal process validation and component quality control. The shelf life of platelet concentrate should be extended from 5 days to 7 or even 8 days, with mandatory bacteriological testing or pathogen inactivation. Another option to increase the platelet supply for prophylactic purposes is to reduce the platelet dose by dividing the existing components. Frozen fresh plasma has the longest shelf life (up to 3 years), so maintaining stable reserves is much safer than for cellular components. Liquid plasma (never previously frozen) has a shelf life of 7-40 days, and can be used in conditions of reduced freezer capacity, shortage of staff working on blood processing or for the production of convalescent plasma. Pathogen inactivation of plasma and platelets allows 3-6 log reduction of SARS-CoV-2 and MERS-CoV. The decision to introduce some of the methods of pathogen inactivation should be made taking into account the costs and resources required for implementation. For countries that do not have pathogenic inactivation already in routine practice, its rapid introduction is a big task. For now, the risk of SARS-CoV-2 transmission through the blood appears to be very low, although our understanding of the virus and behavior during a pandemic will improve over time. In this regard, pathogen inactivation of convalescent plasma should also be considered.